LuxS Involvement in the Regulation of Genes Coding for Hemin and Iron Acquisition Systems in Porphyromonas gingivalis - James, Chloe E. (American Society for Microbiology, 2006)
The periodontal pathogen Porphyromonas gingivalis employs a variety of mechanisms for the uptake of hemin and inorganic iron. Previous work demonstrated that hemin uptake in P. gingivalis may be controlled by LuxS-mediated signaling. In the present study, the expression of genes involved in hemin and iron uptake was determined in parent and luxS mutant strains by quantitative real-time reverse transcription-PCR. Compared to the parental strain, the luxS mutant showed reduced levels of transcription of genes coding for the TonB-linked hemin binding protein Tlr and the lysine-specific protease Kgp, which can degrade host heme-containing proteins. In contrast, there was up-regulation of the genes for another TonB-linked hemin binding protein, HmuR; a hemin binding lipoprotein, FetB; a Fe(2+) ion transport protein, FeoB1; and the iron storage protein ferritin. Differential expression of these genes in the luxS mutant was maximal in early-exponential phase, which corresponded with peak expression of luxS and AI-2 signal activity. Complementation of the luxS mutation with wild-type luxS in trans rescued expression of hmuR. Mutation of the GppX two-component signal transduction pathway caused an increase in expression of luxS along with tlr and lower levels of message for hmuR. Moreover, expression of hmuR was repressed, and expression of tlr stimulated, when the luxS mutant was incubated with AI-2 partially purified from the culture supernatant of wild-type cells. A phenotypic outcome of the altered expression of genes involved in hemin uptake was impairment of growth of the luxS mutant in hemin-depleted medium. The results demonstrate a role of LuxS/AI-2 in the regulation of hemin and iron acquisition pathways in P. gingivalis and reveal a novel control pathway for luxS expression.